SOCIAL AND CULTURAL DETERMINANTS OF UNIVERSITY SOCIAL RESPONSIBILITY - Lesya Chervona; Oksana Bulvinska (Borys Grinchenko Kyiv Metropolitan University, 2021)
The development of human civilization convincingly proves to us that a person, being born in a certain historical epoch in a certain country, prepares not for life in general, but for life in specific social and cultural conditions. Analysis of the available philosophical, pedagogical, sociological literature and areas of scientific and educational research indicates that researchers focus their attention on the problem of social responsibility of modern Universities. In particular, interest in this issue has grown significantly in recent years. The activities of Universities are never limited to the training of future specialists. Universities perform the social function of reproduction and development of society and its systems through the processes of translation of cultural norms in changing historical circumstances, each time on the basis of new social relations. Although among researchers there is no consensus on the definition of social responsibility of the University and the areas of its implementation, there is a general understanding of this phenomenon as a certain obligation of a higher education institution to society. That is why it is important to realize that the social responsibility of Universities should be considered in the context of the general social and cultural dynamics of a particular society. And if there were times when the social responsibility of the University could be represented by the concept of «literacy», then modern world makes completely different demands on education in general and on understanding of the University social responsibility in particular. The social responsibility of the University to society as a social institution, its individual groups and strata, is its commitment to contribute to the solution of important social problems.